2015
DOI: 10.1134/s0021894415040203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of high-quality laser cutting of steel by fiber and CO2 lasers

Abstract: The quality of cutting of low-carbon and stainless steel by beams of fiber and CO 2 lasers with oxygen or nitrogen being used as a process gas is compared. The cut surface roughness for sheets from 3 to 10 mm thick is determined. Domains of optimal (in terms of the minimum roughness criterion) application of lasers of various types in the space of dimensionless parameters (Peclet number and dimensionless power) are found. It is demonstrated that the CO 2 laser is more effective for laser-oxygen cutting, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…This approach has been well approved for the laser cutting of low-carbon and high-alloyed steel sheets by the criterion of the minimal cut surface roughness [12]. The authors have found the areas of the optimal (minimal roughness) application in the dimensional parameter area: the Peclet number Pe = Vb/γ and dimensionless power Be = W/(hλΔT), where λ and γ are the heat-and temperature conductivity coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been well approved for the laser cutting of low-carbon and high-alloyed steel sheets by the criterion of the minimal cut surface roughness [12]. The authors have found the areas of the optimal (minimal roughness) application in the dimensional parameter area: the Peclet number Pe = Vb/γ and dimensionless power Be = W/(hλΔT), where λ and γ are the heat-and temperature conductivity coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…The lens focal distance was 200 mm. Also, the СО 2 laser [5] with a self-filtering resonator was applied; its power reached 8 kW, and the ВРР = 4.7 mm·mrad at the focal distance of the ZnSe lens of 127 and 190 mm.…”
Section: Aw + W Ox = W M + W Condmentioning
confidence: 99%
“…Note that, to have experimental data for each energy flux, the optimal laser power value W, cutting speed V and cut width b, were found for each thickness t, absorption coefficients А and power losses due to the thermal conductivity were measured for these values (measurement techniques are presented in [1,5]. Obtained data enabled to determine the values W m , AW, W cond .…”
Section: Aw = W M + W Condmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the problem of calibrating the hot-wire probe against the velocity was appeared during study characteristics of the flow disturbances in the discharge zone of the CO 2 laser due to great effect of flow disturbances on the power of the laser [12,13]. As far as it was impossible to use any other method for measuring the average and unsteady velocity components, the hot-wire technique has been used [14].…”
Section: Introductionmentioning
confidence: 99%